2014
DOI: 10.1038/srep04049
|View full text |Cite
|
Sign up to set email alerts
|

A New Electrochemical Approach for the Synthesis of Copper-Graphene Nanocomposite Foils with High Hardness

Abstract: Graphene has proved its significant role as a reinforcement material in improving the strength of polymers as well as metal matrix composites due to its excellent mechanical properties. In addition, graphene is also shown to block dislocation motion in a nanolayered metal-graphene composites resulting in ultra high strength. In the present paper, we demonstrate the synthesis of very hard Cu-Graphene composite foils by a simple, scalable and economical pulse reverse electrodeposition method with a well designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(119 citation statements)
references
References 48 publications
2
113
2
2
Order By: Relevance
“…Many previous studies have focused on designing and fabricating new graphene reinforced metal matrix composites, including aluminum [7][8][9], copper [10,11], magnesium [12], and nickel matrix composites [13,14]. In most cases, it was observed that the mechanical properties were significantly enhanced, even with the addition of a very small amount of graphene.…”
Section: Introductionmentioning
confidence: 94%
“…Many previous studies have focused on designing and fabricating new graphene reinforced metal matrix composites, including aluminum [7][8][9], copper [10,11], magnesium [12], and nickel matrix composites [13,14]. In most cases, it was observed that the mechanical properties were significantly enhanced, even with the addition of a very small amount of graphene.…”
Section: Introductionmentioning
confidence: 94%
“…The yield strength of composites was 376 MPa, which was 2.5 times higher than that of copper [4]. Graphene-Cu nanocomposites foils were synthesized by electrochemical way, which showed a high hardness up to 2.2-2.5 GPa and an elastic modulus to 137 GPa, increased by 96% and 30% from those of pure Cu, respectively [5]. Graphene-Al composites were obtained by powder metallurgy technique and exhibited greatly improved mechanical properties after adding graphene [6].…”
Section: Introductionmentioning
confidence: 99%
“…The SEM and HRTEM analysis suggests that there is a close contact between the Cu matrix and the xGnP in the Cu-xGnP composites which contributes in enhancing the mechanical properties of the composites. Graphite nanoplatelets could be found in the grain boundary junctions [4] [35]- [37]. The theoretical density of the various Cu-xGnP composites was calculated using the rule of mixtures where the density of xGnP was 2.1 gm/cc and the density of Cu was 8.9 gm/cc.…”
Section: S N Alam Et Almentioning
confidence: 99%